Influence of basalt powder doses on soybean cultivars (Research, Society and Development, 2020)
The incorporation of basalt powder as a way to promote soil recovery is a current challenge. The work was oriented to evaluate the development of soybean cultivars (SC) after the superficial application of different doses of basalt powder (DBP) in the soil. The experimental delineation used was that of randomized complete blocks, with 3 × 4 factorial arrangement, with three replicas. The treatments were the combination of three SC and four DBP (0, 1, 3 and 5 t ha-1). In the harvest the height of the plants (HP), insertion of the first pod (IFP), number of pods per plant (NPP), number of grains per pod (NGP), mass of one thousand grains (MTG) and yield were determined. of experimental plots (REND). With the harvested grains, they were classified by size in seven sieves of different diameter (Ø7.5 - Ø4.5 mm) and the percentage and relative productivity of grains retained in mesh (RPGRM) were calculated. The results pointed to significant interactions (SC x DBP) (P